2023
DOI: 10.3390/nano13020340
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanocrystalline PuO2 by Hydrothermal and Thermal Decomposition of Pu(IV) Oxalate: A Comparative Study

Abstract: In recent years, the hydrothermal conversion of actinide (IV) oxalates into nanometric actinide dioxides (AnO2) has begun to be investigated as an alternative to the widely implemented thermal decomposition method. We present here a comparison between the hydrothermal and the conventional thermal decomposition of Pu(IV) oxalate in terms of particle size, morphology and residual carbon content. A parametric study was carried out in order to define the temperature and time applied in the hydrothermal conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Properties of PuO2 nanomaterials are different from bulk's ones 31 . For example, when crystallite size is lower than 10 nm, some authors reported lattice parameters above 5.396 Å [32][33][34] . When increasing the surface-to-volume ratio, differences in coordination and surface cause negative stress surface and lattice expansion 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Properties of PuO2 nanomaterials are different from bulk's ones 31 . For example, when crystallite size is lower than 10 nm, some authors reported lattice parameters above 5.396 Å [32][33][34] . When increasing the surface-to-volume ratio, differences in coordination and surface cause negative stress surface and lattice expansion 35 .…”
Section: Resultsmentioning
confidence: 99%
“…A change in agglomerate morphology has been described for all hydrothermally converted oxlates. [5][6][7][8][9][10] This is one of the main differences with thermal conversion, during which the initial oxalate shape is retained. 1,3,23,24 Recrystallisation was also studied from the crystallographic viewpoint.…”
mentioning
confidence: 99%
“…The authors extended their work on the hydrothermal decomposition of various actinide oxalates (Th, U, Np, Pu) 6 and their solid solutions. 7,8 Typically, an oxalate dispersion in pure water (pH adjusted or in the presence of hydrazine) is loaded into an autoclave and treated at 100-250 1C. This procedure results in agglomerates of AnO 2 nanoparticles of approximate size 3 to 10 nm.…”
mentioning
confidence: 99%